The Teacher Perception and the Implementation of Peer Observation at the Language Center in a Private University - Noor Qomaria Agustina; Nur Azima; Edwin Januardie (Universitas Muhammadiyah Yogyakarta, 2020)
One way for the teachers to learn is by peer observation to reflect the practice of teaching which in turn will give input to improve the competence in the teaching learning process. Conducting the process of peer observation need commitment from different parties and raise some problems. The institutions need the human resources and budget allocation to build the system, and to maintain its running. On the other hand, the teachers are reluctant to be observed because they will feel insecure, fear to change the routine, and having more works to do. This research was conducted to answer the following questions: (1) How did teachers perceive and engage in the practice of peer observation at the Language Training Center? and (2) How was the implementation of the peer observation at the Language Center? The research design for this study was the qualitative case study, and took place at the Language Center of a private university in Indonesia. Purposeful sampling was used to determine the participants. The answers of those two questions were the teacher perception in the form of how they perceive the aim of the peer observation as the monitoring evaluation and the benefit of it. Then, the implementation of the Peer Observation and the feedback for the next implementation.